The contributions of the Mamluks to the architecture of the Prophet’s Mosque = Sumbangan dinasti Mamluk kepada senibina Masjid Nabawi - Omer, Spahic (IIUM Press, International Islamic University Malaysia, 2018)
This paper discusses the contributions of the Mamluks to the architecture and development of the Prophet’s Mosque in Madinah. The main discussion lays emphasis on two major issues: Making the Mosque in the Mamluk architectural image, and the maturation of architectural deviations. In order to make them more comprehensible, the two thrusts are preceded by a brief account of a religio-political context that existed prior to and at the time when the Mamluks started to assert their authority, both locally and internationally. In the sheer context of the architectural development of the Mosque, the Mamluks unmistakably showed why they are regarded as some of the greatest patrons of art and architecture in the history of Islamic civilization. But in terms of how they dealt with the prevalent architectural deviations, the Mamluks could be recognized both as victims of the established nonconformist architectural tendencies and trends, and as active protagonists in their further nurturing and spreading. ********************************************************* Kertas kajian ini membincangkan sumbangan ‘Mamluk’ kepada seni bina dan pembangunan Masjid Nabi di Madinah. Perbincangan utama kajian ini menekankan kepada dua isu utama: pembinaan Masjid dalam imej seni bina ‘Mamluk’, dan penyelewengan seni bina. Untuk menjadikannya lebih mudah difahami, terdapat dua teras yang perlu didahului, iaitu satu ringkasan tentang konteks agama-politik yang wujud sebelum zaman penguasaan ‘Mamluk’ dan pada masa ‘Mamluk’ meluaskan kuasa mereka, samada di dalam dan di luar negara. Dalam konteks pembangunan seni bina Masjid, ‘Mamluk’ membuktikan mereka adalah salah satu pelukis seni bina terkemuka dalam sejarah tamadun Islam. Tetapi dari segi menangani penyelewengan seni bina, ‘Mamluk’ juga dikenali sebagai mangsa kepada seni bina yang tidak konvensional, dan sebagai protagonis aktif dalam memupuk dan menyebarkannya.